Analysis of the Influence of Visual, Auditory, and Kinesthetic Learning Styles on Academic Achievement of Middle School Students - Anwar, Firmawati; S, Neviyarni; Mudjiran, Mudjiran (Labor Program Studi Pendidikan Sosiologi, 2024)
This study aims to analyze the influence of visual, auditory, and kinesthetic learning styles on the academic achievement of junior high school students. The research method used is a qualitative approach with a literature review. Data were collected through searching for scientific articles in various academic databases. Data analysis was carried out using a qualitative meta-synthesis approach. The results of the study showed that junior high school students have a variety of learning styles, with a dominance of visual learning styles (45%), auditory (30%), and kinesthetic (25%). Students with visual learning styles excel in subjects involving visual representation, while auditory students excel in language and music subjects. Kinesthetic students show the best performance in practical subjects. Furthermore, the study revealed a complex interaction between learning styles that affect students' academic achievement. The implication of this finding is the importance of developing adaptive learning strategies to accommodate the diversity of students' learning styles.